The importance of preserving deciduous teeth: Assessing knowledge, attitude, and practice of parents of preschool and primary school children in Isfahan - Firoozeh Nilchian; Ehsan Ghasemi (Tehran University of Medical Sciences, 2022)
Background and Aims: There is a traditional belief that the primary teeth can be replaced by permanent teeth and preserving them is not important. The aim of this study was to evaluate the knowledge and attitude of parents of preschool and elementary school children referring to the Specialty Clinic of Isfahan University of Medical Sciences and Imam Hossein pediatric hospital about the importance of preserving deciduous teeth and related factors. Materials and Methods: This descriptive cross-sectional study was performed on 323 parents of preschool and elementary school children referred to the special clinic of Isfahan University of Medical Sciences and Imam Hossein Pediatric hospital. The data collection method was a questionnaire and face-to-face interview. The questionnaire was made, it consisted of 21 multiple-choice questions and descriptive questions. Data were analyzed using descriptive statistics tests and analytical tests such as t-test and Pearson correlation coefficient. Results: The mean score of knowledge of parents was 37.5 with a standard deviation of 16.9, the mean score of attitude was 55.8 with a standard deviation of 11.1 and the mean score of performance was 41.8 with a standard deviation of 15.6 out of 100. Pearson correlation coefficient showed that there was a direct relationship between knowledge, attitude, and performance scores (P<0.001). Parents' knowledge score was directly related to the mothers' and fathers' ages (P<0.001). Conclusion: According to the results, parents' awareness of the importance of the preservation of deciduous teeth and related factors is poor, their attitudes are neutral and their performance is poor to moderate. It is suggested to improve treatment facilities available for children in the family and to educate parents about the preservation of deciduous teeth.